2019
DOI: 10.1016/j.jmig.2018.08.025
|View full text |Cite
|
Sign up to set email alerts
|

Venous Thromboembolism in Minimally Invasive Gynecologic Surgery: A Systematic Review

Abstract: Venous thromboembolism (VTE) is the leading cause of preventable healthcare-related death after surgery. Although there is a large body of research on VTE in the general population as well as risk-assessment tools, evidence specific to the current practices in gynecologic surgery is more sparse. This review article seeks to discuss current literature on VTE in gynecologic surgery, with a focus on minimally invasive surgery. Evidence on risk factors for VTE in gynecologic surgery is evaluated as well as current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…However, the sample size for this study was small ( n = 266). A systematic review by Jorgensen et al., 51 which assessed VTE in minimally invasive gynaecological surgery, showed that the risk of VTE is reduced with MIS, and this is largely attributable to early ambulation, faster postoperative recovery and early discharge from hospital. Despite the reduced risk with laparoscopic surgery, these procedures still carry a risk of thrombosis and an individual risk assessment should be made 44 …”
Section: Thromboprophylaxis For Gynaecological Surgeriesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the sample size for this study was small ( n = 266). A systematic review by Jorgensen et al., 51 which assessed VTE in minimally invasive gynaecological surgery, showed that the risk of VTE is reduced with MIS, and this is largely attributable to early ambulation, faster postoperative recovery and early discharge from hospital. Despite the reduced risk with laparoscopic surgery, these procedures still carry a risk of thrombosis and an individual risk assessment should be made 44 …”
Section: Thromboprophylaxis For Gynaecological Surgeriesmentioning
confidence: 99%
“…Scoring systems have been developed with the intention of identifying patients who need thromboprophylaxis. One such system is the Caprini score, which has been extensively validated in both medical and general surgery patients 51 . VTE guidelines by the ACCP and the European guidelines on perioperative venous thromboembolism prophylaxis are based on the Caprini scoring system.…”
Section: Stratifying Risks For Thromboprophylaxismentioning
confidence: 99%
“…Mechanical thromboprophylaxis (preferably with intermittent pneumatic compression) generally is sufficient for most patients who undergo minimally invasive gynecologic surgery for benign conditions; however, individualized risk assessment should be considered to determine whether additional prophylaxis is indicated based on patient risk factors for VTE. Minimally invasive surgery is independently associated with a decreased incidence of VTE compared with open surgery for benign gynecologic conditions and other open surgical procedures (56)(57)(58). However, factors such as age, surgical complexity, body mass index, cancer, and operative time are associated with an increased incidence of VTE among patients undergoing minimally invasive gynecologic surgery (56,57,(59)(60)(61).…”
Section: Direct Oral Anticoagulantsmentioning
confidence: 99%
“…Minimally invasive surgery is independently associated with a decreased incidence of VTE compared with open surgery for benign gynecologic conditions and other open surgical procedures (56)(57)(58). However, factors such as age, surgical complexity, body mass index, cancer, and operative time are associated with an increased incidence of VTE among patients undergoing minimally invasive gynecologic surgery (56,57,(59)(60)(61).…”
Section: Direct Oral Anticoagulantsmentioning
confidence: 99%
“…Indeed, many of the studies investigating the importance of the mode of surgery on VTE prophylaxis found stronger covariates with VTE from these factors than in the variable of interest, suggesting that we should not forget to consider individual patient factors when deciding on appropriate VTE prophylaxis. It is vital that clinicians consider the mode of surgery as part of the broader VTE risk in the individual, and not as the sole risk‐determining factor 16 …”
Section: Patient Factors Must Be Considered When Determining Vte Riskmentioning
confidence: 99%